CXCL8, MMP1, MMP2, and FN1 Gene Expression and Tumor Extension in Nasopharyngeal Cancer Patients: A Cross-sectional Study - Rahmat Cahyanur; Cosphiadi Irawan; Lisnawati Lisnawati; Marlinda Adham; Achmad Fauzi Kamal; Ahmad R. Handoyo Utomo; Mardiah Suci Hardianti; Muchtaruddin Mansyur; Thariqah Salamah (Interna Publishing, 2023)
Background: There are correlations between tumor staging, lymph node involvement, and patient survival in Nasopharyngeal cancer (NPC) which is one of the most common types of cancer in Indonesia.  The inflammation process plays a role in tumor progression over the long term and this marked by increased proinflammatory cytokine and gene overexpression. This study aims to identify differentially expressed genes (DEGs) in NPC using T and N staging. Methods: This is a cross-sectional study of NPC patients in Cipto Mangunkusumo, Jakarta, between 2018 and 2022. DEGs were identified based on the amount of mRNA detected on paraffin blocks with a 1.5- to -1.5-fold change and an adjusted p-value of <0.05. Results: We included 48 subjects. The mean age of subjects was 47.75 (10.48) years, and most were male (77.1%). Non-keratinized squamous cell carcinoma was the most common histopathology type. Differences in the tumor size of the T4 and non-T4 in metastatic (33.3%) group when compared to the non-metastatic (37.5%) group were insignificant (p = 0.763). The proportion of N3 subjects in the metastatic vs non-metastatic group was different significantly (83.3% vs. 50%, p = 0.030). Gene expression analysis showed that C-X-C motif ligand 8 (CXCL8), matrix metalloproteinase-1 (MMP1), matrix metalloproteinase-1 (MMP2), and fibronectin-1 (FN1) genes of the T4 and non-T4 group to be different significantly. Conclusion: There was significant finding in the N3 subjects of the metastatic and non-metastatic groups. The DEGs of CXCL8, MMP1, MMP2, and FN1 were statistically significant in the T4 when compared to the non-T4 group.